2015
DOI: 10.1111/pin.12364
|View full text |Cite
|
Sign up to set email alerts
|

IgG4‐related disease manifesting the gastric wall thickening

Abstract: IgG4-related disease (IgG4-RD) is a recently designated disease entity and its full picture has not yet been elucidated. Here, we report an unusual case of a patient with gastric wall thickening secondary to IgG4-RD. A 68-year-old male visited our hospital with itchy skin lesions and an episode of organizing pneumonia. On the suspicion of malignancy-associated skin lesions, computed tomography (CT) was performed. The CT revealed prominent thickening of the gastric wall. Due to the possibility of malignancy, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
1
17
0
3
Order By: Relevance
“…Baez et al reported a case of autoimmune pancreatitis with wall thickening and nodular lesions in the gastric wall [22]. Kawano et al also reported gastric lesions in the patients with IgG4-related disease involving the lung [23]. In both cases, the main location of the gastric lesion was submucosal with or without mucosal ulceration.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Baez et al reported a case of autoimmune pancreatitis with wall thickening and nodular lesions in the gastric wall [22]. Kawano et al also reported gastric lesions in the patients with IgG4-related disease involving the lung [23]. In both cases, the main location of the gastric lesion was submucosal with or without mucosal ulceration.…”
Section: Discussionmentioning
confidence: 93%
“…Although IgG4-RD mainly involves glandular tissues or the vascular system, several case reports have shown that IgG4-RD also involves the gastrointestinal tract with ulcer, polypoid lesions, submucosal mass, and wall thickening. However, because of the small number of reports on the gastrointestinal lesions of IgG4-RD, their entire spectrum has not yet been adequately documented, and especially, the radiological aspects of many of these lesions are still obscure [19][20][21][22][23][24][25][26][27][28]. Here, we report the detailed imaging findings in a case of IgG4-RD with gastric involvement.…”
Section: Introductionmentioning
confidence: 99%
“…71 IgG4-RD in the alimentary tract mainly involves glandular tissues or the vascular system of the gastrointestinal tract, resulting in ulcers, polypoid lesions, submucosal masses, and wall thickening. [72][73][74] However, increased numbers of IgG4 þ plasma cells are also identified in patients with other diseases, such as inflammatory bowel diseases.…”
Section: Other Gastrointestinal Manifestationsmentioning
confidence: 99%
“…Aunque existen varias publicaciones, reportes de caso [8][9][10][11][12][13][14][15][16] , el compromiso gástrico es de excepción, siendo nuestro caso el primero descrito en a IgG4. La imagen radiológica mostró marcado engrosamiento de la pared gástrica, con distensibilidad disminuida en la endoscopia, confirmando un compromiso más allá de la mucosa, que incluía las capas musculares.…”
Section: B a Figura 2 A-bunclassified
“…En nuestra experiencia, el compromiso más frecuentemente asociado a la PAI tipo 1 es a nivel de glándulas salivales y conductos biliares 7 , siendo extremadamente raro el compromiso gástrico. A este nivel, se han reportado desde casos esporádicos con úlceras, lesiones polipoideas, masas submucosas y engrosamiento parietal [8][9][10][11][12][13][14][15] , hasta manifestaciones morfológicas y clínicas de síndrome de Ménétrier 16 . Otros también han descrito compromiso de la papila de Vater, demostrando papilitis con infiltración por linfoplasmocitos IgG4 positivos 17,18 .…”
unclassified